Significant loss of retinal nerve fibre layer and contrast sensitivity in people with well controlled HIV disease: implications for aging with HIV - Neelamegam, Malinee; Nawi, Nilani; Bashah, Nor Syuhada Ahmad; Hwei, Yap Siew; Zulhaimi, Nurul Syuhada; Kamarulzaman, Adeeba; Kamaruzzaman, Shahrul Bahyah; Ramli, Norlina; Rajasuriar, Reena (Frontiers in Ophthalmology, 2023)
Objective Antiretroviral therapy has decreased the prevalence of retinal opportunistic infections in people living with HIV (PLWH). However, abnormalities in visual function are evident and may be associated with an early onset of aging in PLWH. In this study, we examined the Retinal Nerve Fibre Layer (RNFL) thickness and visual function in PLWH and HIV non-infected controls in Malaysia. Design Cross-sectional study Methods Two hundred and two (202) PLWH without retinal opportunistic infection and 182 age-matched, HIV seronegative individuals were enrolled. PLWH were recruited from the Infectious Disease clinic at the University Malaya Medical Centre. Controls were recruited among the hospital staff and community volunteers. RNFL thickness was measured with spectral domain optical coherence tomography (SDOCT). Visual functions include visual acuity using LogMAR chart and contrast sensitivity using Pelli- Robson Chart. Results All PLWH (mean age 46.1 years ± 9.9 years) in the study were on ART and 61.2% had a CD4+ T-cell count more than 500 cell/μl. The mean visual acuity was similar between the two groups (LogMAR 0.05 vs. 0.07, p = 0.115). Contrast sensitivity was lower in PLWH compared to HIV seronegative individuals (1.90 vs 1.93, p = 0.032). RNFL thickness was significantly thinner in the temporal quadrant for PLWH compared to controls (68.89 μm vs 74.08 μm, p = 0.001). Conclusion Changes in RNFL thickness and contrast sensitivity were seen in PLWH despite their relatively young age and well controlled HIV disease. The changes reflect structural and functional deficits, and could have long-term implications on their health trajectory.